Organization of plastid genomes in the freshwater red algal order Batrachospermales (Rhodophyta) - Paiano, Monica Orlandi [UNESP]; Del Cortona, Andrea; Costa, Joana F.; Liu, Shao-Lun; Verbruggen, Heroen; De Clerck, Olivier; Necchi, Orlando [UNESP] (Wiley-Blackwell, 2018)
Little is known about genome organization in members of the order Batrachospermales, and the infra-ordinal relationship remains unresolved. Plastid (cp) genomes of seven members of the freshwater red algal order Batrachospermales were sequenced, with the following aims: (i) to describe the characteristics of cp genomes and compare these with other red algal groups; (ii) to infer the phylogenetic relationships among these members to better understand the infra-ordinal classification. Cp genomes of Batrachospermales are large, with several cases of gene loss, they are gene-dense (high gene content for the genome size and short intergenic regions) and have highly conserved gene order. Phylogenetic analyses based on concatenated nucleotide genome data roughly supports the current taxonomic system for the order. Comparative analyses confirm data for members of the class Florideophyceae that cp genomes in Batrachospermales is highly conserved, with little variation in gene composition. However, relevant new features were revealed in our study: genome sizes in members of Batrachospermales are close to the lowest values reported for Florideophyceae; differences in cp genome size within the order are large in comparison with other orders (Ceramiales, Gelidiales, Gracilariales, Hildenbrandiales, and Nemaliales); and members of Batrachospermales have the lowest number of protein-coding genes among the Florideophyceae. In terms of gene loss, apcF, which encodes the allophycocyanin beta subunit, is absent in all sequenced taxa of Batrachospermales. We reinforce that the interordinal relationships between the freshwater orders Batrachospermales and Thoreales within the Nemaliophycidae is not well resolved due to limited taxon sampling.
Keywords: Batrachospermales; conserved genomes; genome rearrangements; infra-ordinal classification; Nemaliophycidae; Rhodophyta